1987
DOI: 10.1002/j.1460-2075.1987.tb04721.x
|View full text |Cite
|
Sign up to set email alerts
|

Human ribophorins I and II: the primary structure and membrane topology of two highly conserved rough endoplasmic reticulum-specific glycoproteins.

Abstract: Ribophorins I and II represent proteins that are postulated to be involved in ribosome binding. They are abundant, highly‐conserved glycoproteins located exclusively in the membranes of the rough endoplasmic reticulum. As the first step in the further characterization of the structure and function of these proteins, we have isolated and sequenced full‐length human cDNA clones encoding ribophorins I and II using probes derived from a human liver expression library cloned into pEX1. The authenticity of the clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 35 publications
(17 reference statements)
5
80
0
Order By: Relevance
“…Likewise, it appears that RI and RII, which are glycosylated in the native state, but not in the yeast two-hybrid system, do not need to be glycosylated to interact with OST48. Evidence that N-glycosylation of RII may not be required for its proper oligomerization and functioning is provided by the fact that, in vivo, only about half of the molecules are glycosylated (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, it appears that RI and RII, which are glycosylated in the native state, but not in the yeast two-hybrid system, do not need to be glycosylated to interact with OST48. Evidence that N-glycosylation of RII may not be required for its proper oligomerization and functioning is provided by the fact that, in vivo, only about half of the molecules are glycosylated (6).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the OST forms an oligomeric complex that sediments in a sucrose gradient as a 10 S particle. This complex was composed of three integral membrane proteins, of which ribophorin I (RI) (5,6) and OST48 (7) are type I transmembrane proteins with most of their polypeptide chains facing the lumen of the ER (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies were newly made against the following peptides: a peptide of the α subunit of the SRP receptor corresponding to positions 137-150 in the amino acid sequence [23] plus a C-terminal cysteine (KKFEDSEKAKKPVRC), a peptide corresponding to the N-terminal 9 amino acids of Sec61β plus a C-terminal cysteine (PGPTPSGTNC), a peptide corresponding to the N-terminal 10 amino acids of RAMP4 plus a C-terminal cysteine (VAKQRIRMANC), a peptide corresponding to the C-terminal 10 amino acids of ribophorin I [5] plus an N-terminal cysteine (CTKIDHILDAL), and a peptide corresponding to the N-terminal 10 amino acids of canine p34 (unpublished data) plus a C-terminal cysteine (TKAGSKGGNLC). These peptides were coupled to keyhole limpet hemocyanin that had been activated with sulfosuccinimidyl 4-(N-maleimidomethyl)cyclohexane-1-carboxylate (sulfo-SMCC).…”
Section: Antibodiesmentioning
confidence: 99%
“…The catalytic OST subunit is present in two paralogous forms, STT3A and B, joined by at least six accessory subunits of poorly understood function: ribophorin I (RibI), ribophorin II (RibII), OST48, DAD1, N33 or IAP, and OST4. Sequence analysis and proteinase protection assays 4 suggest that all OST subunits are integral membrane proteins and many possess substantial lumenal domains, adding up to nearly 200 kDa 2 ( Supplementary Fig. 1).…”
mentioning
confidence: 99%